A new custom-made bivalve brace for pectus carinatum in children and adolescents: preliminary promising experience of 140 patients from a tertiary center - Frediani, Simone; Zarfati, Angelo; Pardi, Valerio; Aloi, Ivan; Bertocchini, Arianna; Accinni, Antonella; Beati, Federico; Pasanisi, Massimiliano; Inserra, Alessandro (Frontiers in Pediatrics, 2024)
Based on the international research on possible novel orthopedic bivalve braces for conservative Pectus carinatum treatment, poor patient compliance was the main cause of tutor failures. Our entire experimental study is based on the hypothesis that a rigid bivalve brace that patients can accept could solve the conservative approach's main problem, poor compliance. It was hypothesized to reduce the classic bivalve brace's thickness and weight to ensure concealment and make it sustainable enough to be worn several hours a day without compromising its therapeutic efficacy.The research ran from January 2020 to December 2022 to follow all participants for at least six months. In 36 months, 140 patients with chest carena deformity were assessed and conservatively treated with the studied guardian, analyzing the bivalve brace's therapeutic efficacy and patient compliance. From the first visit, the parents and patient were informed that this is a 2-year therapeutic course in which the bivalve brace should be worn at least 23 hours a day (with 1 hour of abstinence per day for routine personal hygiene practices). Compliance is the key to therapy success, and the duration of treatment depends on patient adherence.The experimental brace's exceptional effectiveness was confirmed by both the patients' questionnaire (whose satisfaction rate averaged 8.9/10) and a properly selected medical committee's assessment of the therapy's results (whose VAS scale satisfaction was 7.2/10 for symmetric forms and 7.1 for asymmetric ones).In conclusion, the data analyzed confirmed the research hypotheses: first, none of the 140 patients had cardiovascular diseases directly related to their condition, confirming that Pectus carinatum is a pathology of a purely aesthetic nature; second, a cheap, lightweight, and easily obscured brace significantly improved patient compliance.Along with this, the aesthetic aspect's social relevance today may be an important factor in the study cohort's motivation to adhere to therapy. In the past, esthetics and appearance were less relevant at the social level, which may have contributed to the high abandonment and reduced compliance rates of the many studies in the literature.